2017
DOI: 10.1186/s12962-017-0079-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of a universal mass vaccination program with a PHiD-CV 2+1 schedule in Malaysia

Abstract: BackgroundCurrently, two pediatric pneumococcal conjugate vaccines are available in the private market of Malaysia—13-valent pneumococcal conjugate vaccine (PCV13) and pneumococcal polysaccharide and non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV). This study aimed to evaluate the cost-effectiveness of a universal mass vaccination program with a PHiD-CV 2+1 schedule versus no vaccination or with a PCV13 2+1 schedule in Malaysia.MethodsA published Markov cohort model was adapted to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 61 publications
0
37
1
Order By: Relevance
“…The results of our study supported the findings of earlier economic analyses, 10 suggesting higher public health and economic impacts with the adoption of PCV13 into the NIP over PCV10 in Malaysia. Contrary to our results, previous studies by Aljunid et al 9 and Wang et al 11 suggested more cost-savings with a PCV10 program as compared with PCV13. The differences in the predicted outcomes are driven by the differing assumptions used in the economic evaluations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of our study supported the findings of earlier economic analyses, 10 suggesting higher public health and economic impacts with the adoption of PCV13 into the NIP over PCV10 in Malaysia. Contrary to our results, previous studies by Aljunid et al 9 and Wang et al 11 suggested more cost-savings with a PCV10 program as compared with PCV13. The differences in the predicted outcomes are driven by the differing assumptions used in the economic evaluations.…”
Section: Discussioncontrasting
confidence: 99%
“…The differences in the predicted outcomes are driven by the differing assumptions used in the economic evaluations. For instance, Wang et al 11 assumed cross-protection of PCV10 against non-vaccine serotypes such as serotypes 6A and 19A. Although there were some earlier case-control studies which demonstrated the possibility of cross-protection against 19A with PCV10, recent surveillance evidence demonstrates an increasing trend in cases due to 19A in both vaccinated and unvaccinated individuals in countries with a PCV10 program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigational 11-valent vaccine in which all serotypes were conjugated to protein D, a highly conserved protein from NTHi, showed statistically significant efficacy against all AOM episodes due to NTHi [ 60 , 61 ]. Previous economic analyses have assumed an additional benefit for PCV10 in preventing NTHi AOM based on evidence for this investigational 11-valent vaccine [ 47 , 50 , 51 , 62 , 63 ]. However, real-world effectiveness data published over the last few years have presented mixed evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A published Markov cohort model was adapted to simulate the epidemiological burden of pneumococcal and NTHi-related diseases, including IPDs, pneumonia and AOM, within a registered live birth cohort in Taiwan [15,16]. The cohort-based analyses are commonly used for health economic modelling for determining the direct impact of medical interventions [16], and the current model has been used by previous cost effectiveness studies in other countries [17][18][19]. Figure 1 shows the Markov cohort model for the analyses.…”
Section: Markov Modelmentioning
confidence: 99%